New species and new records of Sciophila Meigen (Diptera: Mycetophilidae) from the Afrotropical region - Kurina, Olavi (Zootaxa, 2020)
A comprehensive material of Afrotropical Sciophila including 262 male specimens of 15 species collected from 7 countries are studied. Two new species—S. geiri sp. n. and S. tchabalensis sp. n.—are described from Madagascar and Cameroon, respectively. New records of the following 13 species are presented: S. digitilenta Søli, 1997 (Uganda), S. fenestralis Søli, 1997 (South Africa), S. kakumensis Søli, 1997 (Cameroon, Uganda), S. kjaerandseni Søli, 1997 (Uganda), S. koundensis Søli, 1997 (Uganda), S. leptosoma Søli, 1997 (Democratic Republic of Congo), S. longistyla Søli, 1997 (South Africa), S. mazumbaiensis Søli, 1997 (Uganda), S. ocreata Philippi, 1865 (France: La Réunion), S. papula Søli, 1997 (Democratic Republic of Congo), S. pinniger Søli, 1997 (South Africa, Cameroon, Uganda, Kenya), S. quadra Søli, 1997 (Democratic Republic of Congo), S. stellata Søli, 1997 (Uganda). The majority of the new records represent the first ones since initial description of the species. S. ocreata is considered to be introduced to the Island of La Réunion. The number of Afrotropical Sciophila species is set at 23.